Estrés laboral: relaciones con inteligencia emocional, factores demográficos y ocupacionales - Gabel Shemueli, Rachel (2012)
Occupational stress has become a serious concern within organizations. The purpose of this study is to examine the relations between stress and emotional intelligence, demographic and occupational factors. To accomplish this, two questionnaires were applied to 223 workers from a public organization in Peru and correlations among the variables were analyzed on three levels: the constructs, their dimensions or components and their sub-dimensions. Principle results show that individuals with higher levels of emotional intelligence have less occupational stress. In addition, older professionals and those in senior management and support positions have higher levels of stress in the dimensions of personal resources and personal tension. Conclusions underscore the importance of examining relationships between the variables in order to find solutions to occupational stress and avoid the repercussions this entails. Recommendations are formulated for future studies and practical implications within organizations.